Anarchism and the Avant-Garde : radical arts and politics in perspective - Kosuch, Carolin, 1981- (Avant garde critical studies, 2020)
Anarchism and the Avant-Garde: Radical Arts and Politics in Perspective contributes to the continuing debate on the encounter of the classical anarchisms (1860s−1940s) and the artistic and literary avant-gardes of the same period, probing its dimensions and limits. Case studies on Dadaism, decadence, fauvism, neo-impressionism, symbolism, and various anarchisms explore the influence anarchism had on the avant-gardes and reflect on avant-garde tendencies within anarchism. This volume also explores the divergence of anarchism and the avant-gardes. It offers a rich examination of politics and arts, and it complements an ongoing discourse with theoretical tools to better assess the aesthetic, social, and political cross-pollination that took place between the avant-gardes and the anarchists in Europe.--